Mortality in British hip fracture patients, 2000-2010: a population-based retrospective cohort study. - Klop, C; Welsing, P; Cooper, C; Harvey, N; Elders, P; Bijlsma, J; Leufkens, H; de Vries, F (Elsevier, 2014)
BACKGROUND: Data on recent trends in mortality after hip fracture are scarce. Aims were therefore to examine secular trends in all-cause and cause-specific mortality post hip fracture and to compare this to the general population from 2000 to 2010. METHODS: Population-based cohort study within the United Kingdom Clinical Practice Research Datalink and linked to cause of death data for 57.7% of patients. Patients with a first hip fracture (n=31,495) were matched to up to four controls by age, sex, index date, and practice. All subjects were followed for death, and lifestyle, disease and medication history adjusted hazard ratios (HRs) were calculated. RESULTS: One-year all-cause mortality after hip fracture declined from 2009 and was 14% lower after, compared with before 2009 (22.3% to 20.5%, adj. HR 0.86, 95% CI: 0.81-0.92). The decline was observed for males (≥75years) and females (≥85years). Significant contributors to the decline in mortality post hip fracture were respiratory infections in females as were malignant diseases in males. However, one-year all-cause mortality remained unaltered over the decade when compared to controls with a 3.5-fold and 2.4-fold increased risk in males and females respectively. No significant changes were observed in the relative risks for one-year cause-specific mortality for both genders. CONCLUSIONS: One-year mortality after hip fracture has declined over the last decade in the UK. However, the difference in one-year mortality between hip fracture patients and the general population remained unaltered. These observations highlight the need for the continued implementation of evidence-based standards for good hip fracture care.